The Woman Who Testified: The Pentecostalization of Psychiatry in Yaoundé, Republic of Cameroon. (7th November 2021) - Durham, Elizabeth
Abstract: This article takes a case study approach to the predominance of Pentecostalism, a Christian movement emphasizing conversion and testimony to divine grace, among patients at Sommeil Psychiatric Hospital in Yaoundé, Republic of Cameroon. I argue that certain patients' desire to serve as témoignage (French) or "testimony" (English) to life before and after Sommeil—to the efficacy of biomedical psychiatry—indicates a pattern in which patients drew on their Pentecostal affiliation to navigate psychiatric treatment. Grounded in 24 months of fieldwork with patients and families and hospital staff, I contend that patient experiences of treatment imperfectly paralleled prior and ongoing experiences of Pentecostalism, including cultivation of the desire to convert and testify. Taking this cultivation of desire as a form of subject‐making, I conceptualize the entanglement of religious and therapeutic subjectivities at Sommeil as a patient‐driven "Pentecostalization" of psychiatry, which offers patients plural possibilities and timeframes of health.